Le Congrès des américanistes de Nancy en 1875 : entre succès et désillusions - Étienne Logie; Pascal Riviale (Journal de la Société des Américanistes)
The Nancy congress of Americanists (1875) : successes and disappointments. The first international congress of Americanists opened on July 19th 1875 and was held in the prestigious palace of the Dukes of Lorraine, Nancy. Its instigators, the Société d’Ethnographie and the Société Américaine de France worked in close collaboration with a local board of organization, remarkably led by two prominent notables of Nancy : the Baron Prosper Guerrier de Dumast and Lucien Adam. The congress was a tremendous success and opened up a great tradition. However, little remains of the ambitious concerning American studies which were planned for Nancy : a few scattered museum pieces, asking many unanswered questions, and some distant memories recovered during the celebration of centenary of the first Nancy congress.